The communication of musical expression: as exemplified in jazz performance - White, Christopher K. (Kansas State University, 2010)
This qualitative study sought to inquire into, identify and examine elements of musical expression as exemplified in jazz performance from a phenomenological approach. The purpose was to identify the various elements utilized by expert performers and listeners in perceiving musical expression, to determine whether or not these elements are held in common between performer and listener, and to explore the relation of personal experiences of the phenomenon with aesthetic philosophy and educational practice. Aesthetic concepts were drawn from the writings of Stephen Davies and Peter Kivy while jazz principles and foundations were drawn from Ted Gioia and Gunther Schuller. Ten subjects, five world-class jazz artists and five nationally recognized jazz critics, were selected based upon reputation and professional standing and interviewed in naturalistic settings of their own choosing (home, office, studio). Each subject listened to six recordings of the jazz standard My Funny Valentine as recorded by established jazz icons: Miles Davis, Paul Desmond, Gerry Mulligan, Bill Evans with Jim Hall, Sarah Vaughan, and Keith Jarrett. All were encouraged to comment in a stream-of-consciousness manner while listening to the examples. Additionally, fifteen statements drawn from the literature were read for subjects to rate on a five-point Lykert scale ranging from “totally agree” to “totally disagree”. Interviews were transcribed and coded into themes. Lykert responses were analyzed within group using means and ranges and between groups utilizing difference of means. Results, as interpreted by this researcher, reflect seven themes identified by performers (Sound, Individuality, Virtuosity and Intellect, Communication, Specific Musical Elements, Mood or Character, and Originality and Innovation) and six themes enumerated by critics Individuality, Virtuosity and Intellect, Communication, Specific Musical Elements, Mood or Character, and Originality and Innovation). No attempt was made at stratification of themes, as this was exploratory research. While both groups used the concept of sound, context placed it under the concept of individuality for critics while performers used it more specifically towards the establishment of mood. Lykert responses confirmed strong similarity of thought between the two groups.
Keywords: Jazz; Musical expression; Music education; My Funny Valentine; Phenomenology; Performers and critics; Education, Curriculum and Instruction (0727); Education, Music (0522); Music (0413)